Economic Machining of Hardened Steels by Hard Turning and its Process Variables - Anand, Abhishek; Kumar Behera, Ajay; Ranjan Das, Sudhansu (International Journal of Engineering and Technology, 2018)
Hard turning has evolved as an important machining technique for cutting of hardened steel. In the recent past, increasing use of hard turning in automotive sector has been observed. Hard turning is greatly affected by factors like machine tool, tool geometry, cutting tool materials, cutting parameters, and lubrication as well as cooling methods. This paper presents all the factors that influences hard turning operations performance and is an attempt to give a proper understanding of the process. This paper further discuss, in brief, about cylindrical grinding and its comparison with hard turning, which confirms the elimination of long technological chain of traditional production process by implementing hard turning with appropriate selection of abovementioned process variables.Â Â